Organisational factors and academic research agendas: an analysis of academics in the social sciences - Horta, H. (2019)
The demands for academic research placed on contemporary universities are closely related to the levels of innovative research they are expected to produce. Concurrently, both governments and university management strive to make the production of academic research more cost-efficient and have implemented measures to ensure this. Top-down policies influenced by the concepts of new public management and managerialism have been introduced, pushing for competitiveness and increased performativity in academic research setups. These policies and guidelines have been criticised by academics as having eroded collegiality and autonomy, which are considered necessary to achieve quality research. The focus of this study is on the social sciences and aligns with this critique, demonstrating that autonomy and collegiality are the key organisational features fostering multidisciplinary, collaborative and riskier research agendas that lead to breakthroughs. Academics with high levels of organisational commitment are more likely to create research agendas that assume more conservative, discipline-bound and risk-averse traits, with less potential to achieve the intended innovative research outcomes.